First finding of impact melt in the IIE Netschaëvo meteorite. (12th January 2016) - van Roosbroek, N.; Pittarello, L.; Greshake, A.; Debaille, V.; Claeys, P.
Abstract: About half of the IIE nonmagmatic iron meteorites contain silicate inclusions with a primitive to differentiated nature. The presence of preserved chondrules has been reported for two IIE meteorites so far, Netschaëvo and Mont Dieu, which represent the most primitive silicate material within this group. In this study, silicate inclusions from two samples of Netschaëvo were examined. Both silicate inclusions are characterized by a porphyritic texture dominated by clusters of coarse‐grained olivine and pyroxene, set in a fine‐grained groundmass that consists of new crystals of olivine and a glassy appearing matrix. This texture does not correspond to the description of the previously examined pieces of Netschaëvo, which consist of primitive chondrule‐bearing angular clasts. Detailed petrographic observations and geochemical analyses suggest that the investigated samples of Netschaëvo consist of quenched impact melt. This implies that Netschaëvo is a breccia containing metamorphosed and impact‐melt rock (IMR) clasts and that collisions played a major role in the formation of the IIE group.